Gustave Roussy immune score as an independent prognostic factor for treatment response and survival in advanced renal cell carcinoma treated with nivolumab in second-line and beyond - Erdoğan, Bülent; Gökmen, İvo; Elpen Kodaz, Cagnur; Küçükarda, Ahmet; Divriklioğlu, Didem; Bayrakçı, İsmail; Hacıbekiroğlu, İlhan; Engin, Esra Özen; Hacıoğlu, Muhammet Bekir; Özcan, Erkan; Öztürk, Gökhan; Kodaz, Hilmi (Frontiers in Oncology, 2025)
BackgroundMetastatic renal cell carcinoma (mRCC) represents a significant challenge due to variable patient outcomes despite advancements in treatment. Nivolumab, a programmed death-1 (PD-1) inhibitor, has demonstrated efficacy as a second-line or later therapy following progression on tyrosine kinase inhibitors (TKIs). However, identifying reliable prognostic biomarkers remains critical. The Gustave Roussy Immune (GRIm) score, incorporating serum albumin, lactate dehydrogenase (LDH), and neutrophil-to-lymphocyte ratio (NLR), may provide prognostic value in this context.MethodsThis multicenter retrospective cohort study included 81 mRCC patients treated with nivolumab as second-line or subsequent therapy following progression on first-line TKIs (e.g., sunitinib or pazopanib). Patients were categorized into low (0–1) and high (2–3) GRIm score groups based on pre-treatment laboratory values. Outcomes included progression-free survival (PFS), overall survival (OS), and treatment response, assessed using RECIST criteria. Survival analyses were performed using Kaplan-Meier curves, and prognostic factors were identified through univariate and multivariate analyses.ResultsThe median age was 63 years, and 72.8% were male. Patients with low GRIm scores demonstrated significantly higher objective response rates (44.4% vs. 11.1%; p = 0.01) and longer OS (23.3 vs. 8.8 months; p = 0.004). PFS was also significantly longer in the low GRIm score group (8.7 vs. 3.1 months; p = 0.015). Multivariate analysis identified a high GRIm score as an independent predictor of worse OS (HR: 0.46; p = 0.03).ConclusionThe GRIm score effectively stratifies mRCC patients treated with nivolumab, identifying those with significantly better survival and treatment responses. As a simple, cost-effective tool, it offers potential for integration into clinical practice to guide personalized treatment strategies. Further prospective studies are warranted to validate these findings.